DISARTICULATION OF STUDENT VOICES AND STATE LEGITIMACY IN ONLINE MEDIA DISCOURSE: A CRITICAL ANALYSIS 2022–2024: - - Siti Suwadah Rimang; Jusmaeni; Mufliha Khaeratih Agus; Suhardi (PT. Jurnal Center Indonesia Publisher, 2025)
This study examines how online media frames student demonstrations and how student voices are disarticulated in the news, especially in relation to the state's legitimacy strategy. The study period covers 2022 to 2024, when the intensity of the student movement increased in response to various public policy issues. The main purpose of this research is to uncover the practice of digital mainstream media representation of student actions and dissect the ideological power relations between state actors and civil society groups in the realm of media discourse. The approach used is Norman Fairclough's three-dimensional model of Critical Discourse Analysis (AWK), which includes analysis at three levels: textual structure (lexical and syntactic), discourse practice (the process of production and consumption of texts), and social practice (ideological and institutional context). Five news articles from Kompas.com were analyzed in depth as the main sample. The results of the study show that online media tends to frame student actions through dictionaries that reduce the meaning of their struggle, such as